1984
DOI: 10.3354/meps018253
|View full text |Cite
|
Sign up to set email alerts
|

Energetic parameters of a population of Chlamys varia (Bivalvia: Pectinidae)

Abstract: Energy relations of a population of black scallop Chlamys varia (L.) in Lanveoc (Bay of Brest, France) were studied from 1976 to 1978. The population had a production of 538.52 Kcall00 mu' and of 497.10 Kcal 100 m"' during the years 1976 to 77 and 1977 to 78, respectively; it assimilated 5773.21 Kcal 100 m-' during the first year and 4561.21 Kcal 100 m"' during the second year of this study. Net production efficiency of black scallops (9 to 12 %) was very low compared to that of other bivalve populations repor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
1

Year Published

1985
1985
2004
2004

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(6 citation statements)
references
References 14 publications
(23 reference statements)
1
4
1
Order By: Relevance
“…There was some annual variation in the turnover ratio in scallops from 10 m (1982 > 1983 > 1981) and in those from 31 m (1982, 1983 > 1981). Our observations are consistent with those of Shafee & Conan (1984) for Chlamys varia, in which there is a decrease in the turnover ratio in older animals and also year-to-year variation in PIB.…”
Section: Differences Related To Water Depthsupporting
confidence: 81%
“…There was some annual variation in the turnover ratio in scallops from 10 m (1982 > 1983 > 1981) and in those from 31 m (1982, 1983 > 1981). Our observations are consistent with those of Shafee & Conan (1984) for Chlamys varia, in which there is a decrease in the turnover ratio in older animals and also year-to-year variation in PIB.…”
Section: Differences Related To Water Depthsupporting
confidence: 81%
“…Likewise, the net growth efficiencies (NGE) reported in this study rank amongst the lowest reported for bivalves (see Newell 1983, Shafee andConan 1984). The comparatively low levels of assimilation recorded in the present study (metabolic rates were however similar to previously reported values for cockles : Boyden 1972, Newell andBayne 1980), point to restrictive environmental conditions for growth, probably extremely limited food availability coupled with long-lasting periods of emersion (mean: 45% air exposure).…”
Section: Annual Growth and Reproductive Strategycontrasting
confidence: 32%
“…These changes comprised a decrease in citrate synthase activity or in the concentrations of high-energy phosphates, as well as a lowering of intracellular pH. An exponential decrease in K 2 with increasing age is well documented for bivalves (Fuji & Hashizume 1974, Alimov 1981, Shafee & Conan 1984, Iglesias & Navarro 1991, Urrutia et al 1999. In some cases (Rodhouse 1978, Vahl 1981) K 2 declines rapidly until maturity is reached and then tends to level off.…”
Section: Discussionmentioning
confidence: 96%